Perfil de mulheres usuárias de álcool em ambulatório especializado em dependência química - Elbreder, Márcia Fonsi [UNIFESP] (2008)
Although the number of women who use, abuse of and become addicted to alcohol is increasing, they are still not the main target of the health care services as their distinctive characteristics regarding psychoactive substances have not been taken into account by the public health policy decision-makers. OBJECTIVE: To characterise those women who use alcohol as well as to identify the pattern of alcohol consumption, clinical interventions, and previous treatments performed in this patient population. METHODS: This retrospective cohort study reviewed medical records of alcohol users who had sought treatments offered by UNIAD and UNIFESP between 2000 - 2006. A total of 192 patients were included in this study according to criteria for treatment dropout. RESULTS: The groups were found to have similar socio-demographic characteristics. Consumption of both fermented and distilled beverages were significantly higher in the dropout group (p = 0.002). Alcohol addiction was found to be significantly more severe in both groups (p < 0.001). Use of auxiliary medication (p < 0.001) and search for psychiatric consultation (p < 0.001) were significantly higher in the non-dropout group. CONCLUSION: Alcoholic women who abandoned the treatment during the first month, compared to those who did not, made more use of both fermented and distilled beverages, had consumed less units per week, used less auxiliary medications, and sought less treatments.